Pengaruh Capital Intensity, Kepemilikan Institusional, Beban Pajak Tangguhan, dan Manajemen Laba terhadap Agresivitas Pajak - Uswa Azizah; Ratna Herawati; Retno Indah Hernawati; Bambang Minarso (Universitas Riau Kepulauan, 2025)
This research examines the impact of capital intensity, institutional ownership, deferred tax expense, and earnings management on tax aggressiveness in mining companies registered on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The research purposes to present empirical data on how internal company factors shape tax aggressiveness, especially in an industry with substantial asset investment and strict regulatory oversight. This study uses quantitative study based on existing data extracted from annual financial statements and analyzes the variables through multiple linear regression. The analysis indicates which capital intensity and institutional ownership have a significant impact on tax aggressiveness, indicating which asset investment and institutional monitoring play an important role in corporate tax strategies. In contrast, deferred tax expense and earnings management do not significantly affect tax aggressiveness, suggesting that temporary differences between accounting and fiscal profit, as well as income manipulation practices, are not utilized as tools for tax minimization. Sampling was conducted using the puposive sampling method and the population of 90 was obtained which was used as a sample of 17 companies and data processing using the SPSS 25.